Pengembangan Bahan Ajar Mata Kuliah Konversi Energi Berbasis Teknologi: Development of Technology-Based Energy Conversion Course Teaching Materials - Rizki Wijaya; Edi Setiyo (Universitas Pendidikan Ganesha, 2025)
This study aims to develop technology-based Energy Conversion course teaching materials using the Canva application in the form of valid and practical E-Modules. The background of this study is the limitations of conventional teaching materials that are less interactive and have not utilized technology optimally, which causes low student interest and understanding of the material. The research method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects of the study were students of Mechanical Engineering Education, Sriwijaya University, class of 2022. The validation results by material experts and media experts showed that the E-Module developed was in the